Evaluation of peritoneal CEA levels following colorectal cancer surgery. Issue 4 (7th June 2014) - Berkovich, Liron; Shpitz, Baruch; Ghinea, Ronen; Greemland, Itzhak; Kravtsov, Vladimir; Kidron, Debora; Mishaeli, Moshe; Avital, Shmuel
<x xml:space="preserve">Abstract</x> Background Peritoneal carcinoembryonic antigen (pCEA) levels in the early postoperative period following a curative resection of colorectal cancer (CRC) have not been previously studied. Methods Postoperative peritoneal fluids of 36 CRC patients followed by 24 benign colonic disease patients were evaluated for CEA levels and tumor cell presence. Serum CEA levels were also evaluated prior and after surgery. Results Although high postoperative pCEA levels were observed in some benign patients, more CRC patients exhibited significant elevation of postoperative pCEA (>5 ng/ml) compared to benign patients (50% vs. 23%, P = 0.039). Postoperative median pCEA levels of CRC patients were significantly higher compared to benign patients (5.4 vs. 2 ng/ml, P = 0.011). Specifically, pCEA levels in CRC patients were significantly elevated when measured during the first 24 hr after surgery. Postoperative pCEA levels were associated with colon tumor location compared to rectal location. However, no correlation was found with known risk factors for cancer recurrence or with serum CEA levels. Conclusions Postoperative pCEA levels may be significantly elevated following a curative resection for CRC. Its significance within patient's prognostic evaluation remains to be studied. Inclusion of patient's follow‐up data may reveal the significance of elevated pCEA levels following CRC resection. J. Surg. Oncol. 2014; 110:458–462. © 2014 Wiley Periodicals, Inc.